2013
DOI: 10.1590/s0103-84782013000900017
|View full text |Cite
|
Sign up to set email alerts
|

Quadrados mínimos parciais uni e multivariado aplicados na seleção genômica para características de carcaça em suínos

Abstract: RESUMO A principal contribuição da genética molecular é a utilização direta das informações de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Chromosome 1 also presented a higher importance for the ETUL, ETL, and ETO traits, similar to results found by Beeckmann et al (2003), Rohrer and Keele (1998), and Azevedo et al (2013b).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Chromosome 1 also presented a higher importance for the ETUL, ETL, and ETO traits, similar to results found by Beeckmann et al (2003), Rohrer and Keele (1998), and Azevedo et al (2013b).…”
Section: Discussionsupporting
confidence: 84%
“…In addition, the accuracy for the variables LR, LL, L, and BCD showed higher values than those obtained from GWS methodologies based on the dimensionality reduction presented by Azevedo et al (2013b).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The high percentage of coincidence between rankings of the multi- and single-trait models may be, as already mentioned, due to the fact that the genetic correlation between the traits was not significant. Genetic merit estimates of individuals, whether or not they consider genomic information, are in general estimated more accurately when they are based on analyses that consider all the traits simultaneously–that is, under a multivariate approach [ 40 , 41 ]. In a study with popcorn half-sib families, [ 42 ] found that multi-trait BLUP (Best Linear Unbiased Prediction) was more accurate and efficient in family selection than single-trait BLUP.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, studies proposing and testing the efficiency of multi-trait genomic selection in plant breeding programs should be developed. The regression method via partial least square (PLS) can be an efficient alternative for allowing the multi-trait selection (Azevedo et al 2013). The general purpose of PLS is the formation of components that capture the highest amount of information possible from the explanatory variables to predict the principal dependent variable (Boulesteix and Strimmer 2007).…”
Section: Plant Breedingmentioning
confidence: 99%